Given the arithmetic sequence in the question, we can deduce that the common difference, d, is 4 and the first term, a1, is 4. The below formula will be used to solve for the 60th term of the sequence;
![a_n=a_1+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/8ad7drcg9vuq9sminhqfaw7j3r5r4u1ij9.png)
Where a1 = first term = 4
d = common difference = 4
n = number of term = 60
Let's go ahead and substitute the given values into our equation;
![\begin{gathered} a_(60)=4+(60-1)4 \\ =4+(59)4 \\ =4+236 \\ =240 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2b0fqu03l397q0v8f8sg9zyimxx6ogt8zx.png)
Therefore, the 60th term of the sequence is 240.